Nature's clocks : how scientists measure the age of almost everything - Macdougall, J. D., 1944- (University of California Press, 2008)
Radioactivity is like a clock that never needs adjusting, writes Doug Macdougall. "It would be hard to design a more reliable timekeeper." In Nature's Clocks, Macdougall tells how scientists who were seeking to understand the past arrived at the ingenious techniques they now use to determine the age of objects and organisms. By examining radiocarbon (C-14) dating?the best known of these methods?and several other techniques that geologists use to decode the distant past, Macdougall unwraps the last century's advances, explaining how they reveal the age of our fossil ancestors such as.